Migrants’ Acculturative Stress: Comparing British and Japanese Female Migrants in the Netherlands - Rijk, Menthe Wilhelmina Maria Catharina (Student Undergraduate Research E-journal!, 2017)
Research on the different causal factors of acculturative stress – with an emphasis on cultural distance as causal factor – was conducted by interviewing British and Japanese female migrants residing in the Netherlands. The results showed that besides actual cultural distance, perceived cultural distance might also cause acculturative stress. Moreover, the behaviour of others (e.g. locals, family) during the migration process also appeared to influence acculturative stress experience. Additionally, if (perceived) cultural distance was the main factor of the migrants’ acculturative stress, they were likely to experience acculturative stress for a longer duration than migrants whose acculturative stress was mainly caused by the attitudes and behaviours of those around them. Lastly, the results indicated that bi-cultural self-efficacy largely determines to what extent migrants regard cultural distance as stressful or not.